Comparative analysis of landscape terms in Uzbek and English and usage of terms - Shakhnoza Usmanova (Genius Journals, 2022)
The article describes the analysis of Uzbek philology, kinship terms, style, usage, language history, comparative landscape terms
Keywords: Landscape; term; philology; linguistics